Mediator’s Criminal Responsibility for Special Offences in Terms of Victim-Offender Mediation - Fahri Gökçen Taner; Yaprak Öntan (Ceza Hukuku ve Kriminoloji Dergisi)
In recent years, the application and scope of mediation in criminal procedures expanded with the tendency to extensificate alternative dispute resolution methods. Given the current situation, the criminal responsibility of the mediator should be discussed and determined in light of their obligations. The mediator is a public official performing a duty from the moment of their appointment to the moment they submit their report. Therefore, perpetrators may receive more severe punishment for certain crimes committed because of the mediator duty. However, the mediator’s public official role may also lead to criminal liability for some special offenses2 and heavier penalties in terms of others. This article evaluates the circumstances for which the mediator can be held responsible due to their official capacity.